The relationship between game genres, learning techniques and learning styles in educational computer games - Rapeepisarn, K.; Wong, K.; Fung, C.; Khine, Myint Swe (2008)
Educational computer game has many similar characteristics like any other genres of games. However its particular aspect is designed to teach, and in which main objective involves in learning a topic. To develop an effective educational computer game, different game genres, learning activities and techniques, and learning styles are important issues for consideration. This paper presents an analysis by comparing and establishing relationships between the game genres and learning techniques based on the types of learning and potential game style of Prensky [1] and learning styles based on the study of Chong et al. [2]. © 2008 Springer-Verlag Berlin Heidelberg.